Educação corporativa : a educação percebida na administração de empresas - Braga, José Carlos (2013)
Generate competitive advantages is one of the great challenges of contemporary companies. The Business Administration, during the twentieth century, went through a set of changes in understanding about what an organization is. At the end of the century was reached to a business model more "organic", focused both in their internal relations as the external, in people and in learning. The Corporate Education has as one of his biggest challenges to develop innovative and creative professionals that meet the demands of these contemporary organizations.To this has been used in an intentional or not practices already deeply studied in the field of Education. This research aims to demonstrate concepts of education which are already used in Business Administration through corporate education, and how some of these concepts are put into practice. To achieve this goal, will be presented understandings of Corporate Education present in Natura Cosmetics, and also the result of practical observation program leadership development of this company, that called Cosmos